PENGARUH PRODUK DAN PROMOSI TERHADAP KEPUTUSAN MENJADI NASABAH TABUNGAN MARHAMAH PADA PT. BANK SUMUT CABANG SYARIAH PADANGSIDIMPUAN - Gautama Siregar, Budi (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
The problem of this research is the number of banking institutions that operate in sharia, creating competition among banking institutions in collecting funds from the community. Evidently, the decision to become a customer of Savings Marhamah at PT. Bank SUMUT of the Sharia Branch of Padangsdimpuan which declines in 2016. Therefore, the bank can offer its products with a better strategy and expand the range and the promotional media. This type of research is descriptive quantitative research. With data source that is primary data. With a population of 8119 customers, with sampling technique using random sampling technique as much as 99 customers. Data collection techniques used are questionnaires and documentation. And tested the validity and reliability. Descriptive test and linearity test. Prerequisite test includes normality test, heteroscedasticity test and multicollinearity test. And multiple linear regression analysis techniques. The results of this study show partially (t test) states that, Product has tcount ttabel (1.667 1.660) and significance level Î± (0.099 0.1) means Product significantly influence to Customer's Decision. Promotion has t count ttable (2.100 1.660) and significance level Î± (0,038 0,1) means that Promotion has significant effect to Customer's Decision. The result of simultaneous research (F test) states that Product and Promotion have Fcount Ftable (5.371 2.36) and significance level obtained (0.006 0,1) means Product and Promotion simultaneously have a significant effect to Customer's Decision. While R Square equal to 0.216, it means Customer Decision influenced by Product and Promotion equal to 21.6%, while the other 78.4% is explained by other variable not included in this research.